FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR PERIODE 2017-2019 - Dewi Fortuna; Merry Susanti (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to obtain empirical results regarding the influence ofinstitutional ownership, intellectual capital, firm size, and sales growth on the value ofcompanies listed in the IDX for 2017-2019. The population of this study is all manufacturingcompanies listed in the Indonesia Stock Exchange for 2017-2019. The sample selected bypurposive sampling method based on certain criteria and considerations is 40 companies. Thisresearch was processed using multiple linear regression analysis with the help of statisticalsoftware program Eviews v12.0 (Econometric Views version 12). The results of the study basedon multiple linear regression analysis showed that all the independent variables used had nosignificant effect on the dependent variable of firm value.